MRPL53, a New Candidate Gene for Orofacial Clefting, Identified Using an eQTL Approach. (January 2018) - Masotti, C.; Brito, L.A.; Nica, A.C.; Ludwig, K.U.; Nunes, K.; Savastano, C.P.; Malcher, C.; Ferreira, S.G.; Kobayashi, G.S.; Bueno, D.F.; Alonso, N.; Franco, D.; et al.
A valuable approach to understand how individual and population genetic differences can predispose to disease is to assess the impact of genetic variants on cellular functions (e.g., gene expression) of cell and tissue types related to pathological states. To understand the genetic basis of nonsyndromic cleft lip with or without cleft palate (NSCL/P) susceptibility, a complex and highly prevalent congenital malformation, we searched for genetic variants with a regulatory role in a disease-related tissue, the lip muscle (orbicularis oris muscle [OOM]), of affected individuals. From 46 OOM samples, which are frequently discarded during routine corrective surgeries on patients with orofacial clefts, we derived mesenchymal stem cells and correlated the individual genetic variants with gene expression from these cultured cells. Through this strategy, we detected significant cis -eQTLs (i.e., DNA variants affecting gene expression) and selected a few candidates to conduct an association study in a large Brazilian cohort (624 patients and 668 controls). This resulted in the discovery of a novel susceptibility locus for NSCL/P, rs1063588, the best eQTL for the MRPL53 gene, where evidence for association was mostly driven by the Native American ancestry component of our Brazilian sample. MRPL53 (2p13.1) encodes a 39S protein subunit of mitochondrial ribosomes and interacts with MYC, a transcription factor required for normal facial morphogenesis. Our study illustrates not only the importance of sampling admixed populations but also the relevance of measuring the functional effects of genetic variants over gene expression to dissect the complexity of disease phenotypes.